2014
DOI: 10.1111/vco.12120
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transplant malignant neoplasia associated with cyclosporine‐based immunotherapy: prevalence, risk factors and survival in feline renal transplant recipients

Abstract: The study objective was to compare the prevalence of malignant neoplasia in feline renal transplant recipients (n = 111) with a control population of cats that did not receive transplantation (n = 142); and to determine whether the development of post-transplant malignant neoplasia (PTMN) affects long-term survival. Twenty-five (22.5%) renal transplant recipients were diagnosed with PTMN, and of those 14 (56%) were diagnosed with lymphoma. The overall survival time in cats that developed PTMN following renal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Feline renal transplant recipients treated with cyclosporine face a similar increased risk of malignant neoplasia [ 25 ]. The most commonly reported cancer is lymphoma, with feline transplant recipients having 6.7 times higher odds of developing diffuse large B cell lymphoma compared to matched controls [ 33 , 34 ]. Whether a gammaherpesvirus is involved in the etiology of these lymphomas in cats, as it is in over 75% of PTLD in humans, is not yet clear [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feline renal transplant recipients treated with cyclosporine face a similar increased risk of malignant neoplasia [ 25 ]. The most commonly reported cancer is lymphoma, with feline transplant recipients having 6.7 times higher odds of developing diffuse large B cell lymphoma compared to matched controls [ 33 , 34 ]. Whether a gammaherpesvirus is involved in the etiology of these lymphomas in cats, as it is in over 75% of PTLD in humans, is not yet clear [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…80 Malignancy, most commonly lymphoma, has been reported in cats receiving long-term ciclosporin. 114,121,122 Cats receiving chronic ciclosporin therapy following renal transplantation are at six times higher risk of both developing a malignant tumor and of lymphoma. 122 ✜ Chlorambucil A limited number of cats with NRIMHA have responded to treatment with chlorambucil as an adjunct to glucocorticoid therapy.…”
Section: Immunosuppressive Treatment Of Primary Medullary Causes Of Nmentioning
confidence: 99%
“…Second, immunosuppressive drugs themselves have oncogenic effects, such as a reduction in the ability for DNA repair, induced by cyclosporine [1, 8]. Although such reports are limited in veterinary medicine, a few studies have been reported, in which the incidence of development of malignant tumors, especially lymphoma, was increased by cyclosporine-based immunosuppressive therapy after renal transplantation in cats [16, 24, 25]. Although the relationship between administration of cyclosporine and development of HCC was reported in rats [11], it is not clear in humans, felines and canines.…”
mentioning
confidence: 99%